“Use 19 Metal Pieces of Approximately the Same Timbre”. An Analysis of Twelve Recorded Performances of Xenakis’s Métaux (Pléïades) - Diederik Mark de Ceuster (Zeitschrift der Gesellschaft für Musiktheorie, 2021)
The sixxen is a microtonal percussion instrument designed by Iannis Xenakis for Métaux and Mélanges from his 1978 composition Pléïades. The instructions for building this instrument are non-specific; the timbre of the instrument and its specific pitch content are up for the constructor to determine. This has resulted in a number of various sixxen sets used by numerous ensembles that are completely different in their (microtonal) temperament, microtonal pitch series, ambitus, and timbre. This article seeks to explore the aesthetic impact of the indeterminate building instructions of the sixxen by comparing performances of various ensembles and their sixxen sets. Referring both to spectral analysis and the listener’s experience, this article analyzes twelve performances of Métaux for their pitch content and timbre. In the preface to the score of Pléïades, Xenakis describes that the primordial element of the work is rhythm; strong periodic elements are repeated, and then superposed to form “arhythmic clouds of sound.” In comparing the various sixxen sets, this article shows that in some performances the periodic elements are heavily emphasized, whereas in others the sixxens increase the merging of sounds, which de-emphasizes rhythmic structures in favor of so-called “arhythmic clouds.”